Empowering or addicting? An analysis of the effects of team members–supervisor relationships on job satisfaction in healthcare. (April 2022) - Ciasullo, Maria Vincenza; Douglas, Alexander; Palumbo, Rocco
Patient-centredness relies on integrated care, which requires teamwork to be effectively implemented. Positive relationships between team members and supervisors are crucial to enhance health professionals' satisfaction with their job and, consequently, to increase their commitment to organizational excellence. However, the positive effects of team members–supervisor exchange may dilute when the team is endowed with autonomy at work. The article proposes a moderation analysis aimed at collecting evidence of the implications of team members–supervisor relationships on job satisfaction (JS) with team autonomy (TA) as a moderating variable. Results of the study suggest that positive exchanges between team members and supervisors enhance health professionals' satisfaction with their job. However, TA acts as a negative and statistically significant moderator. Good exchanges between team members and their supervisor seem to lose their positive effects on JS when health professionals are provided with a greater self-determination to accomplish their organizational activities. Tailored management interventions should be designed to sustain teamwork when increased autonomy at work is assigned to health professionals.